2022
DOI: 10.3171/2021.5.spine202003
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant teriparatide therapy targeting the osteoporotic spine: influence of administration period from the perspective of bone histomorphometry

Abstract: OBJECTIVE Teriparatide (TPTD) is a potent promoter of early-stage osteogenesis and may be a useful adjuvant therapy to reduce complications related to bone fragility in spinal surgery patients with osteoporosis. However, effective neoadjuvant TPTD therapy regimens remain poorly understood. This study aimed to examine the effect of preoperative TPTD administration on cancellous bone with bone histomorphometry and to clarify the timing of preoperative TPTD administration for patients with spinal fusion and osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…First, the administration period could be too short to provide a substantial anabolic effect in the TPTD group. A histomorphometric analysis revealed that bone formation significantly increases at least 3 months after TPTD treatment ( Sawakami et al, 2022 ). Second, in previous reports, a higher prevalence of OVF was associated with an increased risk of subsequent OVF ( Hagino et al, 2013 ; Lindsay et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the administration period could be too short to provide a substantial anabolic effect in the TPTD group. A histomorphometric analysis revealed that bone formation significantly increases at least 3 months after TPTD treatment ( Sawakami et al, 2022 ). Second, in previous reports, a higher prevalence of OVF was associated with an increased risk of subsequent OVF ( Hagino et al, 2013 ; Lindsay et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Second, the duration of preoperative TPTD treatment was significantly shorter in the PJF group than in the non-PJF group. Sawakami et al 16 recommended that the optimal duration of preoperative TPTD treatment is 3 months or more in terms of osteoporotic complication rate, clinical score, and bone histomorphometry. Our results further corroborate this, as the average duration of preoperative TPTD treatment was ~3 months in the non-PJF group.…”
Section: Discussionmentioning
confidence: 99%
“…We chose a regimen of four months based off the authors’ experience with neoadjuvant teriparatide in ASD surgery as well as the current literature on the timing of its anabolic effects. Sawakami et al 24 noted that mineralizing bone surface in iliac crest biopsies, a major indicator of new bone formation, starts to increase after one month of teriparatide treatment and peaks at about four months. In a similar study, Lindsay et al 42 noted that only one month of teriparatide treatment was necessary for significant bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…We varied the estimates by (±10%). The choice of a four-month treatment regimen was determined based on clinically important minimal time necessary for peak teriparatide anabolic effects 24. The probability of reoperation failure and requiring a third operation was presumed to be 21% (±10%), based on published reports 25…”
Section: Methodsmentioning
confidence: 99%